PENGGUNAAN MEDIA GADGET DALAM AKTIVITAS BELAJAR DAN PENGARUHNYA TERHADAP PERILAKU ANAK - Zuli Dwi Rahmawati (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2020)
In the era of globalization, information and communication technology is developing very rapidly and brings great influence in various fields, one of them is education. Education is greatly helped by the presence of technology that supports learning activities that are more varied and creative. The existence of gadget learning media lately is very popular with children ranging from pre-school age to elementary school, even the intensity of time to use the gadget is more than the time socializing with family or the environment. The use of learning media must be accompanied by parental assistance and supervision, because in addition to having a positive impact, the negative impact of the gadget is also very large. Learning activities with gadget media have a significant influence on children's behavior, because at the age of development the child learns by seeing, listening, observing, recording and imitating, especially if there is no supervision and control so that the child will be active on gadgets and passive in social activities.